مساهمة الاستثمار في رأس المال البشري في تسيير المعرفة بالمؤسسة الاقتصادية الجزائرية - خليفي, عيسى; قوادرية, ربيحة (جامعة الوادي University of Eloued, 2014)
مما لاشك فيه أن رأس المال البشري أصبح من ضروريات اقتصاد المعرفة، على اعتبار أن رأس المال البشري من أهم مصادر اكتساب الميزة التنافسية نظرا لارتباطه بشكل أساسي بالمعرفة التي تعتبر من أهم مكوناته، ولكون المعرفة عملية معقدة فإن تسييرها يعتبر من أهم التحديات التي تواجهها المؤسسات من أجل اكتسابها وتوليدها وخزنها ونشرها وتوزيعها وتطبيقها، ومن أجل تسيير ناجح وكفؤ للمعرفة لبد من الاستثمار في هذه المعارف والمهارات والخبرات وذلك من خلال استقطاب أفضل المواهب وتطويرهم والمحافظة عليهم، لذلك جاءت هذه الدراسة لمعرفة "مساهمة الاستثمار في رأس المال البشري في تسيير المعرفة بالمؤسسة الاقتصادية الجزائرية"، بالاعتماد على دراسة حالة مؤسسة صناعة الكوابل–فرع جنرال كابل بسكرة- وأظهرت الدراسة أن الاستثمار في رأس المال البشري يساهم في تسيير المعرفة بالمؤسسة الاقتصادية الجزائرية، حيث بينت النتائج أن الاستثمار في رأس المال البشري يساهم في اكتساب المعرفة، كما يساهم الاستثمار في رأس المال البشري في توليد المعرفة، و أيضا يساهم الاستثمار في رأس المال البشري في نشر وتوزيع المعرفة، وأخيرا يساهم الاستثمار في رأس المال البشري في تطبيق المعرفة act: There is no doubt that human capital has become a necessity of knowledge economy, on the grounds that the human capital of the most important sources of gain competitive advantage because of its connection primarily with the knowledge which is one of the most important components, and the fact that knowledge is a complex process, the conduct is considered one of the most important challenges faced by institutions for acquisition and generation, storage, dissemination and distribution, and application, in order to conduct a successful and efficient knowledge must be to invest in knowledge, skills and expertise through attracting the best talent and develop and maintain them, therefore, this study was to find out "contribution of the investment in human capital in knowledge management in the Algerian economic institution", depending on the case study institution cable industry - Branch General Cable Biskra-, the study showed that the investment in human capital contribute in knowledge management in the Algerian economic institution, where results clarify that the investment in human capital contribute in knowledge acquisition, and investment in human capital contribute in knowledge generation, and also investment in human capital contribute in knowledge dissemination and distribution, finally investment in human capital contribute in knowledge application.
دراسة حالة مؤسسة صناعة الكوابل – فرع جنرال كابل بسكرة
مقال- مجلة رؤى اقتصادية
Keywords: رأس المال البشري، الاستثمار في رأس المال البشري، تسيير المعرفة، عمليات تسيير المعرفة: human capital, investment in human capital, knowledge management, process knowledge management